The 4G/5G Sequence Polymorphism in the Promoter of Plasminogen Activator Inhibitor-1 (PAI-1) Gene: Relationship to Plasma PAI-1 Level in Venous Thromboembolism - Stegnar, Mojca; Uhrin, Pavel; Peternel, Polona; Mavri, Alenka; Salobir-Pajnič, Barbara; Stare, Janez; Binder, Bernd R. (Thrombosis and Haemostasis, 1998)
Impaired fibrinolysis due to increased plasminogen activator inhibitor-1 (PAI-1) is observed in up to 40% of patients with venous thromboembolism and might be causally related to the disease. There is evidence that genetic variations in the promoter of the PAI-1 gene and metabolic factors contribute to increased plasma PAI-1 levels.A single nucleotide insertion/deletion (4G/5G) polymorphism in the promoter region of the PAI-1 gene and metabolic factors were studied in 158 unrelated patients below the age of 61 years (43 ± 11 years, mean ± standard deviation) with history of objectively confirmed venous thromboembolism and in 145 apparently healthy controls.Patients had on average two times higher PAI activity (11.9 vs. 6.1 IU/ml) and by 40% higher PAI-1 antigen (14.8 vs. 10.7 ng/ml) than healthy controls, and also higher body mass index, lipid levels, fasting glucose and insulin. Patients differed significantly from healthy controls neither in the frequency of the 4G and 5G alleles (0.57/0.43 in patients and 0.52/0.48 in controls) nor in the distribution of the 4G/5G genotypes. Possession of the 4G/4G or the 4G/5G genotype did not increase relative risk for venous thromboembolic disease and the distribution of the 4G/5G genotypes was neither associated with recurrent nor with spontaneous disease. In patients association between the 4G/5G genotypes and PAI activity (adjusted for body mass index, triglyceride and glucose level) was observed, with the highest PAI activity values in the 4G/4G genotype (14.6 IU/ml), intermediate in the 4G/5G genotype (13.3 IU/ml) and the lowest in the 5G/5G genotype (5.2 IU/ml, all values means). Association between PAI activity and triglyceride level was the strongest in the 4G/4G genotype (correlation coefficient r = 0.47, p <0.01) and the weakest in the 5G/5G genotype (r = -0.04, not significant).In conclusion, the present case-control study shows an association between the 4G/5G polymorphism in the promoter of the PAI-1 gene and plasma PAI-1 levels in patients with venous thromboembolism. Similar distribution of the 4G/5G genotypes in patients and healthy controls suggests that this genetic variation by itself is not a major risk factor for venous thromboembolism.